Etika Dalam Pengajaran Etika di Masyarakat Majemuk - Gunardi Endro (Respons: Jurnal Etika Sosial, 2017)
ABSTRAK: Dalam perspektif pendidikan akhlak/moral, pengajaran etika di masyarakatmajemuk yang peserta didiknya memeluk agama dan menghayati kebudayaanlokal yang berbeda-beda memiliki suatu tantangan yang tidak ringan. Misi daripendidikan akhlak/moral secara singkat dapat dirumuskan sebagai suatu upayauntuk meningkatkan kemauan dan kemampuan peserta didik untuk berbuat baik.Masalahnya, etika sebagai refleksi kritis-filosofis seringkali dianggap menawarkanalternatif standar moral ideologis yang bersaing dengan standar moral yang sudahterlebih dahulu diyakini peserta didik melalui penghayatan agama dan kebudayaanlokalnya. Disini diajukan argumen bahwa, meskipun pengajaran etika diperlukanuntuk membuat pendidikan akhlak/moral efektif mencapai tujuannya, peranetika sebaiknya tidak mengambil alih peran agama dan kebudayaan lokal dalampendidikan akhlak/moral. Peran etika dan peran agama dan kebudayaan lokalseharusnya saling melengkapi. Peran etika lebih pada pengembangankemampuanpeserta didik untuk berbuat baik, sementara peran agama dan kebudayaanlokallebih pada penguatan kemauan peserta didik untuk berbuat baik. Dengan adanyaketerbatasan peran etika itu, pengajaran etika di masyarakat majemuk memerlukanetika tersendiri untuk menjaga sinergi antar peran sehingga pendidikan akhlak/moral efektif mencapai tujuannya. Enam prinsip etika diajukan disini sebagaipegangan dalam mengajarkan etika, yaitu otonomi, tanggung jawab, transparansi,keadilan, kepedulian, dan profesionalisme.KATA KUNCI: pendidikan moral, pengajaran etika, agama, kebudayaan lokal, etika pengajaranABSTRACT: In the perspective of moral education, teaching of ethics in a pluralistic society whose learners embrace various different religions and live up to various different localcultures has a serious challenge. Te mission of moral education can briefly be definedas an effort to develop the will and the ability of learners to do good. Te problem isthat ethics as a critical-philosophical reflection is often perceived to offer an alternativeideological moralstandard in competition with moral standards which have been firstlybelieved by thelearners through appreciation of their religions and local cultures. This paper provides an argument that, though teaching of ethics is indeed required to makemoral education effectively achieve its objective, the role of ethics ought not to take overthe role of religions and local cultures within the framework of moral education. Ethics,religion, and local culture should complement each other. Te role of ethics should bemore on developing the learners’ ability to do good, while the role of religions and localcultures should be more on strengthening the will of the learners to do good. Given thelimited role of ethics, teaching of ethics in a pluralistic society requires ethics of its own tomaintain a synergy between the two roles so that moral education effectively achieves itsobjective. Six ethical principles are here proposed as a guide in teaching ethics, namely:autonomy, responsibility, transparency, justice, caring, and professionalism.KEY WORDS: moral education, teaching of ethics, religion, local culture, ethics ofteaching